2012
DOI: 10.3354/meps09698
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal interaction between sediment and microphytobenthos in a temperate estuarine macro-intertidal bay

Abstract: Intertidal flats of the estuarine macro-intertidal Baie des Veys (France) were investigated to identify spatial features of sediment and microphytobenthos (MPB) in April 2003. Gradients occurred within the domain, and patches were identified close to vegetated areas or within the oyster-farming areas where calm physical conditions and biodeposition altered the sediment and MPB landscapes. Spatial patterns of chl a content were explained primarily by the influence of sediment features, while bed elevation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 31 publications
5
37
0
Order By: Relevance
“…The fluctuation of biomass of the uppermost cm of sediment peaked around the emersion period at noon. Similar to previous studies (Blanchard et al, 2001;Orvain et al, 2012), the tidal rhythm was observed to have an influence on the chl a concentration, however, the effect was masked by other effects described in this study. The presence of the gastropod Peringia ulvae was a key parameter controlling the MPB biomass and the main differences observed between seasons were probably caused by grazing pressure.…”
Section: Biofilm Developmentsupporting
confidence: 90%
See 2 more Smart Citations
“…The fluctuation of biomass of the uppermost cm of sediment peaked around the emersion period at noon. Similar to previous studies (Blanchard et al, 2001;Orvain et al, 2012), the tidal rhythm was observed to have an influence on the chl a concentration, however, the effect was masked by other effects described in this study. The presence of the gastropod Peringia ulvae was a key parameter controlling the MPB biomass and the main differences observed between seasons were probably caused by grazing pressure.…”
Section: Biofilm Developmentsupporting
confidence: 90%
“…1B) were defined by the wood stakes. Each day, three replicate squares were chosen randomly according to the sampling design described in a previous field study (Orvain et al, 2012). In these squares, surficial sediment was sampled hourly from the beginning (0 hour after area emersion) to the end of emersion (3 hours after area emersion), leading to four sampling times during every emersion periods.…”
Section: Study Site and Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPM concentration is generally higher than 100 g•m −3 in the waters adjacent to the northern mudflats, and lower than 20 g•m −3 in the southern area [31][32][33]. Phytoplankton growth is limited by too high SPM concentration in the most turbid waters, but high concentration of chlorophyll-a (Chl-a), over 10 mg•m −3 , has been documented in the vicinity of the tidal flats [31,34] and is due to the resuspension of benthic microalgae [35]. …”
Section: Study Sitementioning
confidence: 99%
“…Oxygen measurements are then usually upscaled to larger areas using several models of PP MPB developed for the purpose (Pinckney and Zingmark, 1993;Serôdio and Catarino, 2000). Regardless of the method used, seasonal and spatial patterns of PP MPB , similarly to MPB biomass, have been explained by a wide array of biotic and abiotic environmental variables depending on the environment studied Jesus et al, 2009;Orvain et al, 2012;Savelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%